The Menacing Grip of Gangs in Romeo and Juliet:A Literary Evidential Analysis (International Journal of Scientific Research and Management (IJSRM), 2024)
Often admired for its portrayal of young love, William Shakespeare and his “Romeo and Juliet” tragedy likewise delve into the menacing impact and theme of gang violence. This research considers how Shakespeare uses the violent clashes in the play to expose the social and family structures of his time, the renaissance, highlighting the impact of gang mentality on districts and families. Through a qualitative, historical, and literary methodological approach, the research takes a close look at the key scenes in the play, the consequences of the territorial fights, and the behavior of the characters to prove that that gang violence is behind the deaths of the protagonists. The prime discovery revealed that the feud between the Montagues and Capulets reflected and are crucial to impact both society and inner family safety. The findings suggest that Shakespeare uses gang violence as a powerful metaphor to explore how rivalries can negatively impact both unity of a community and individual destinies. This research serves in attempting to bond both classical literature and modern social concerns, relating tactics and recitals, as a novel way to view, break down, and prove the historic existence of gang violence.